Assessing Person-Job Fit for Careers as Remotely Piloted Aircraft Sensor Operators. Issue 3 (1st October 2020) - Carretta, Thomas R.; Romay, Sophie; Mouton, Amanda; Deregla, Andrew; Clark, Angela; Barron, Laura G.
ABSTRACT: Objective: Recent US Air Force occupational surveys indicated that while job satisfaction is high for Remotely Piloted Aircraft (RPA) Sensor Operators (SO), a high percentage do want to reenlist. The objective was to assess factors that affect their job satisfaction and retention. The results will help guide development of Realistic Job Preview (RJP) videos for new recruits considering an RPA SO career. Background: Despite burgeoning demand and insufficient manning for RPAs to conduct intelligence, surveillance, and reconnaissance activities, research on the factors that contribute to operator job satisfaction and retention has been limited. Method: One hundred ten RPA SOs were surveyed to assess factors thought to affect person-job fit. Thematic content analysis by independent raters was done to provide insight into factors that (1) may make the RPA career field a good or poor fit, (2) unique challenges and rewards of the career field, (3) misconceptions about the career field, and (4) job characteristics influencing retention decisions. Results: A high level of agreement (mean Cohen's kappa = 0.73) occurred across pairs of raters. The strongest content themes indicated having a direct effect on the battlefield was rewarding (65.1%), adjusting to shift work was challenging (64.7%), and the job entailed a high level of responsibility (56.3%). Conclusion: Qualitative data may provide insight regarding factors affecting person-job fit and guide development of selection tools such as RJPs.